Maskulinitas Dalam Iklan U Mild "Sepanjang Jalan Kenangan" - Alvina Sa’adilla (Jurnal Ilmu Komunikasi, 2021)
This research was conducted to find out the symbols or signs of masculinity that appear in U Mild's advertisement "Along Jalan Kenangan". This research is a qualitative research using semiotic content analysis method. Researchers conducted an analysis of images or scenes contained in advertisements that show signs or symbols of masculinity. According to. The results of this study indicate that in the U Mild Along Jalan Kenangan advertisement, there are 4 scenes, namely scenes of rock climbing and show off the sportifity, camping in the forest, riding a big motorcycle in the rain and watching a rock concert which contains symbols of masculinity such as big muscles in men. in the rock climbing scene and there is a falling scene showing that the sport is dangerous, in the camping scene in the forest it shows courage and an adventurous spirit as a masculine man and also shows a hunting scene which depicts the mentality of a man who is brave in men, in the scene then shows the adventurous spirit of men, namely riding a big motorbike together when it rains, showing that men are not limited even though rainstorms occur but can still be hit and show strength as men with big body muscles. As well as accessories typical of masculine men such as black clothes, black leather jackets, which are used in scenes of riding motorbikes together and seeing music concerts together which show solidarity and sportsmanship.”